Long-term risk of screen-detected and interval breast cancer after false-positive results at mammography screening: joint analysis of three national cohorts - Román, Marta; Hofvind, Solveig; von Euler-Chelpin, My; Castells, Xavier (British journal of cancer, 2019)
Background We assessed the long-term risk of screen-detected and interval breast cancer in women with a first or second false-positive screening result. Methods Joint analysis had been performed using individual-level data from three population-based screening programs in Europe (Copenhagen in Denmark, Norway, and Spain). Overall, 75,513 screened women aged 50–69 years from Denmark (1991–2010), 556,640 from Norway (1996–2008), and 517,314 from Spain (1994–2010) were included. We used partly conditional Cox hazards models to assess the association between false-positive results and the risk of subsequent screen-detected and interval cancer. Results During follow-up, 1,149,467 women underwent 3,510,450 screening exams, and 10,623 screen-detected and 5700 interval cancers were diagnosed. Compared to women with negative tests, those with false-positive results had a two-fold risk of screen-detected (HR = 2.04, 95% CI: 1.93–2.16) and interval cancer (HR = 2.18, 95% CI: 2.02–2.34). Women with a second false-positive result had over a four-fold risk of screen-detected and interval cancer (HR = 4.71, 95% CI: 3.81–5.83 and HR = 4.22, 95% CI: 3.27–5.46, respectively). Women remained at an elevated risk for 12 years after the false-positive result. Conclusions Women with prior false-positive results had an increased risk of screen-detected and interval cancer for over a decade. This information should be considered to design personalised screening strategies based on individual risk.